Atrial Infarction-Induced Spontaneous Focal Discharges and Atrial Fibrillation in Sheep: Role of Dantrolene-Sensitive Aberrant Ryanodine Receptor Calcium Release. (March 2018) - Avula, Uma Mahesh R.; Hernandez, Jonathan J.; Yamazaki, Masatoshi; Valdivia, Carmen R.; Chu, Antony; Rojas-Pena, Alvaro; Kaur, Kuljeet; Ramos-Mondragón, Roberto; Anumonwo, Justus M.; Nattel, Stanley; Valdivia, Héctor H.; Kalifa, Jérôme
Abstract : Background: The mechanisms underlying spontaneous atrial fibrillation (AF) associated with atrial ischemia/infarction are incompletely elucidated. Here, we investigate the mechanisms underlying spontaneous AF in an ovine model of left atrial myocardial infarction (LAMI). Methods and Results: LAMI was created by ligating the atrial branch of the left anterior descending coronary artery. ECG loop recorders were implanted to monitor AF episodes. In 7 sheep, dantrolene—a ryanodine receptor blocker—was administered in vivo during the 8-day observation period (LAMI-D, 2.5 mg/kg, IV, BID). LAMI animals experienced numerous spontaneous AF episodes during the 8-day monitoring period that were suppressed by dantrolene (LAMI, 26.1±5.1; sham, 4.3±1.1; LAMI-D, 2.8±0.8; mean±SEM episodes per sheep, P <0.01). Optical mapping showed spontaneous focal discharges (SFDs) originating from the ischemic/normal-zone border. SFDs were calcium driven, rate dependent, and enhanced by isoproterenol (0.03 µmol/L, from 210±87 to 3816±1450, SFDs per sheep) but suppressed by dantrolene (to 55.8±32.8, SFDs per sheep, mean±SEM). SFDs initiated AF-maintaining reentrant rotors anchored by marked conduction delays at the ischemic/normal-zone border. NOS1 (NO synthase-1) protein expression decreased in ischemic zone myocytes, whereas NADPH (nicotinamide adenine dinucleotide phosphate, reduced form) oxidase and xanthine oxidase enzyme activities and reactive oxygen species (DCF [6-carboxy-2′, 7′-dichlorodihydrofluorescein diacetate]-fluorescence) increased. CaM (calmodulin) aberrantly increased [ 3 H]ryanodine binding to cardiac RyR2 (ryanodine receptors) in the ischemic zone. Dantrolene restored the physiological binding of CaM to RyR2. Conclusions: Atrial ischemia causes spontaneous AF episodes in sheep, caused by SFDs that initiate reentry. Nitroso–redox imbalance in the ischemic zone is associated with intense reactive oxygen species production and altered RyR2 responses to CaM. Dantrolene administration normalizes the CaM response, prevents LAMI-related SFDs, and AF initiation. These findings provide novel insights into the mechanisms underlying ischemia-related atrial arrhythmias. Abstract : Supplemental Digital Content is available in the text.